Satisfacción del cliente en el Comercial “Ferreriego” en la parroquia San Juan – cantón Pueblo Viejo periodo 2023. - Vera García, Hugo Johan (2024)
The purpose of this research study is to clearly determine the type of prestige of customer service in the competitive area of the agricultural sector, specifically in the Ferriego commercial located in the parish of San Juan, Pueblo Viejo, during the period 2023. For this purpose, a methodology was applied, specifically the hypothetical deductive methodology, using a descriptive and field research approach with a non-experimental design, the study covered the entire population, which is made up of 55 recurring customers, therefore without the need to use formulas. statistics such as sampling due to the small size of the population or data collection, which was carried out through surveys directed at clients and interviews applied to the company manager. Subsequently, the information collected was analyzed and interpreted with the support of software specialized in data analysis. The results showed that customer service directly affects the competitiveness of the business. However, various deficiencies in the care provided were identified, which generates dissatisfaction in clients. In response to this problem, several strategies were proposed to improve. The quality of service, these strategies include a detailed plan with specific activities, responsible implementation deadlines and assigned budget with the objective of optimizing customer service in the company.